Semiotika Sosial dalam Video Klip Uniwara Mengukir Prestasi untuk Negeri (Kajian Analisis Wacana Multimodal) - Basyid, Mokh. Abdul; Firmansyah, M. Bayu (Multiverse: Open Multidisciplinary Journal, 2023)
This research aims to determine the form of multimodal discourse in the Uniwara Carving Achievements for the Country video clip so that it can strengthen the message and intent to be conveyed. A video clip is a short video that accompanies music, generally a song to promote a record album. Multimodal is a term used to refer to the way people communicate using different modes at the same time which is defined as the use of several semiotic modes in product design, or semiotic events simultaneously, and in certain modes. Therefore, this research was conducted to describe the multimodal form in the video clip Uniwara Carving Achievements for the Nation. This research uses multimodal discourse analysis with a social semiotic approach. The research results found five forms of multimodality in the video clip Uniwara Carving Achievements for the Country. The five multimodal forms include language, image, music, sound and movement modalities.